Pengaruh Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada CV. Klambi Abadi Garment Kota Depok - Chintia Zakiyah; Ibnu Sina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to determine the effect of compensation and work motivation on employee performance at CV. Klambi Abadi Garment, both partially and simultaneously with an associative approach. This research employed a quantitative method. The sample used in this study consisted of 78 respondents. Data were collected through questionnaires using a Likert scale as the measurement instrument, while data processing was conducted using SPSS version 26. The data analysis techniques included validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, as well as t-tests and F-tests. The analysis results indicate that: (1) Partially, compensation has a positive effect on employee performance at CV. Klambi Abadi Garment. This is evidenced by the regression equation Y = 20.051 + 0.489X₁ and the t-test result tcount = 5.005 > ttable = 1.992 with a significance value of 0.000 < 0.05. (2) Partially, work motivation has a positive effect on employee performance at CV. Klambi Abadi Garment. This is proven by the regression equation Y = 20.578 + 0.497X₂ and the t-test result tcount = 4.105 > ttable = 1.299 with a significance value of 0.000 < 0.05. (3) Simultaneously, compensation and work motivation have a positive effect on employee performance at CV. Klambi Abadi Garment. This is evidenced by the multiple linear regression equation Y = 13.407 + 0.384X₁ + 0.319X₂, a correlation coefficient of 0.558, and a coefficient of determination of 0.311, indicating that compensation and work motivation contribute 31.1% to employee performance. The F-test result shows Fcount = 16.951 > Ftable = 3.119 with a significance level of 0.000 < 0.05